EVALUATION OF THE POTENTIAL OF PECTIN FROM UNRIPE BANANA (MUSA ACUMINATE X BALBISIANA VAR.CARDABA) PEEL FOR JACKFRUIT (ACTOCARPUS HETEROPHYLLUS LAM) MARMALADE APPLICATIONS - Tanaid, Reciel Ann B; Tiu, Ann Myril C (Journal of Agriculture and Technology Management, 2020)
Waste utilization from food processing industries is a highly crucial and challenging task all around the globe. Utilization of the fruit processing co-products into fruit preserves such as marmalade is a favorable venture. However, due to its very low pectin content, it is necessary to fortify the formulation with pectin. This study aimed to evaluate the food application of pectin from banana peel. The pectin was used in the processing of jackfruit marmalade made of jackfruit trimmings and seed coat. Varying levels of pectin (0%, 0.5%, 1%, 1.5%, 2% and 2.5%) were added to the jackfruit marmalade formulation. The sensory attributes, general acceptability, and physico-chemical characteristics of the product were evaluated. The levels of banana peel pectin significantly influenced the color, texture, spread ability, and general acceptability of the product. The pH and total soluble solids also gave significant results. The mean general acceptability for the jackfruit marmalade is 7.59, corresponding to “like moderately’’ in the 9-point Hedonic scale. For the consumer preference test, consumers liked and preferred both commercial and extracted pectin for marmalade production. Furthermore, jackfruit marmalade was much preferred by the consumers compared to a commercially available orange marmalade. The cost of producing 500 g of jackfruit marmalade made from jackfruit trimmings, seed coat, and banana peel pectin is Php 265.22.